Black Experience in New Mexico 1974 - 1980 - Office of African American Affairs, New Mexico (Albuquerque, NM University of New Mexico, 1980)
This DVD set is a collection of unedited footage of events that took place during the years of 1974-1980. Dr. Harold Bailey donated these DVD's to the NMOAAA in 2010. The " Black Experience in New Mexico" is an anthology that allows the public to access certain historical events relevant to African Americans in the State of New Mexico. As one will see, Dr. Harold Bailey and others played a key role in the movement to improve conditions for youth, faculty, student athletes, and the Black community as a whole.
The Athletic Boycott at UNM - 1974; A Tribute to Black Women/Summer Youth Program - 1975; Youth Enrichment Day - 1976; Roots and Rise of Black Leadership in NM - 1977; New Mexico Black Studies Consortium - 1978; The Black Student Athlete 0 1979; and the State of Black Affiars in NM - 1980.
NMSL Document #: NM H 211.81:B 49 "Special thanks go to KOAT-TV, KOB-TV and KNME-TV for documenting these events in partnership with the Afro-American Studies Program at the Univeristy of New Mexico.
Keywords: Dr. Harold Bailey, donor; African American affairs - New Mexico. -- History - African American - New Mexico